Validation of a core patient-reported-outcome measure set for operationalizing success in multimodal pain therapy: useful for depicting long-term success? - Carolin Donath; Christa Geiß; Christoph Schön (BMC, 2018)
Abstract Background The study aims to validate a previously developed and published combined success criterion for patients after multimodal pain therapy (Donath et al., BMC Health Serv Res 15:272, 2015). The criterion classifies treated patients as successful in the long term on the basis of pain severity, disability through pain, depressiveness, and health-related quality of life. Methods Routine longitudinal data of 135 pain patients treated with multimodal pain therapy in 2014-2015 at the Interdisciplinary Pain Center of the University Clinic Erlangen were available at baseline, therapy start, therapy end, and 12 months after treatment. Patients were, on average, 51.0 (SD 11.1) years old and to 63.7% female, two thirds were employed (66.7%). We conducted an analysis of concurrent validity (with: pain severity, disability through pain, depressiveness, mental and physical quality of life), criterion validity (with disability days, self-rated success), convergent validity (with stress, anxiety, well-being), and discriminant validity (with chronicity of pain, comorbidity), objectivity, and reliability. Statistically, descriptive and inference statistics, graphical methods and MANOVAs were used. Results Patients classified as successful had significantly better values on the 5 variables demonstrating concurrent validity (all p < .001), significantly fewer Disability days (M = 15.31 (SD = 23.15) vs. M = 26.75 (SD = 29.15)); t (133) = 2.308; p = .024, less Anxiety (Pillai-Spur: F (3, 131) = 2.972, p = .034), less Stress (Pillai-Spur: F (3, 131) = 9.907, p < .001), and better Well-being (Pillai-Spur: F (3, 131) = 9.594, p < .001) 12 months after treatment than patients classified as not successful. The Spearman correlation between success classification and Chronicity stage was .094 (p = .280). Conclusion We demonstrated the validity of the combined success criterion with long-term data in addition to confirming the reliability and objectivity of the criterion. Future research might consider identifying predictors of success in multi-modal pain therapy.